An Analysis of Theories Supporting Agile Scrum and the Use of Scrum in Systems Engineering. Issue 2 (2nd April 2020) - Bott, Mitch; Mesmer, Bryan
Abstract: Agile methods have become popular in software development as they offer ways to adapt to constant change during development. Agile methods have begun to be employed on non-software systems. The methods used for development on any type of system should be derived from established theories to ensure the methods enable success in development. A better understanding of Agile methods and the theories behind them can aid engineering managers in the selection of an appropriate development process for engineered systems. In this article, theories supporting Agile and Model-Based Systems Engineering (MBSE) methodologies are reviewed and found to be a key enabler of Agile methods for systems engineering. A process for performing Agile systems engineering using a model-based approach for complex systems addressing steps identified in the INCOSE systems engineering handbook is presented.